2019
DOI: 10.3389/fpubh.2019.00235
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing for Surveillance of Diphtheria in Low Incidence Settings

Abstract: Corynebacterium diphtheriae ( C. diphtheriae ) is a relatively rare pathogen in most Western countries. While toxin producing strains can cause pharyngeal diphtheria with potentially fatal outcomes, the more common presentation is wound infections. The diphtheria toxin is encoded on a prophage and can also be carried by Corynebacterium ulcerans and Corynebacterium pseudotuberculosis . Currently, across Europe, infections are mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 173 publications
3
17
0
Order By: Relevance
“…To this aim, we characterized phenotypically and genotypically a large sample of C. diphtheriae isolates from diverse geographic and temporal origins. We confirmed that the species is made of multiple phylogenetic sublineages [ 9 , 13 , 67 ] and showed that homologous recombination contributes five times more to their diversification than mutation, consistent with previous evidence of recombination in C. diphtheriae populations [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…To this aim, we characterized phenotypically and genotypically a large sample of C. diphtheriae isolates from diverse geographic and temporal origins. We confirmed that the species is made of multiple phylogenetic sublineages [ 9 , 13 , 67 ] and showed that homologous recombination contributes five times more to their diversification than mutation, consistent with previous evidence of recombination in C. diphtheriae populations [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…The other limitation of this study was we did not examine the deoxyribonucleic acid (DNA) sequence of C. diphtheriae to analyze the association between the genetic aspect and the MIC. Genetic information is suggested to be done regularly [62]. Further study may be focused in this issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not have data relating to the patient's travel history. Diphtheria disease will remain a health problem due to the movement of people (Sadoh and Oladokun 2012;Seth-Smith and Egli 2019). Thus, the information on the travel history of infected patients is important to predict the potential transmissions within one country or among countries, so this disease could be prevented in the future.…”
Section: Resultsmentioning
confidence: 99%